ANAPLASTIC KAPOSI SARCOMA MIMICKING ANGIOSARCOMA - Teixeira, Vera (2014)
Introduction: Angiosarcoma is the most common vascular tumor in the context of chronic lymphedema, known as Stewart-Treves syndrome. However, it is known that Kaposi's sarcoma is often accompanied by lymphedema (often precedes the onset of typical lesions), and occasionally distinguishing between Kaposi's sarcoma and angiosarcoma may be a diagnostic challenge.Clinical case: We present the case of a male patient, 69 years-old, with an erythematous-violaceous plaque on the left arm associated with chronic lymphedema. Histologic examination showed a proliferation of epithelioid cells in the dermis, associated with cytologic atypia and presence of slit-like vascular spaces evocative of angiosarcoma. However, the clinicopathological correlation associated with molecular biology (PCR) allowed the diagnosis of anaplastic Kaposi's sarcoma. Comments: Our case highlights the difficulty in differentiating this variant of Kaposi's sarcoma from angiosarcoma and the spectrum of clinical and histologic overlap between these two entities.